Psychological distress among Ugandan adolescents living with HIV: Examining stressors and the buffering role of general and religious coping strategies. Issue 12 (2nd December 2017) - Mutumba, Massy; Bauermeister, Jose A.; Harper, Gary W.; Musiime, Victor; Lepkowski, James; Resnicow, Ken; Snow, Rachel C.
ABSTRACT: HIV infection increases the risk of psychological distress among adolescents living with HIV (ALHIV), which, in turn, increases risky behaviours such as medication non-adherence, substance use, and sexual risk-taking. The majority of studies on psychological distress among ALHIV have been conducted in high-income countries; data on the prevalence and correlates of psychological distress among ALHIV in sub-Saharan Africa (SSA) are scarce, yet over two-thirds of the global population of ALHIV resides in SSA. The purpose of this study was to identify the contextually relevant correlates of psychological distress among Ugandan ALHIV. Utilizing the stress and coping framework, we explored the risk and protective factors for psychological distress in cross-sectional sample of 464 ALHIV (aged 12–19; 53% female) at a large HIV treatment centre in Kampala, Uganda. The stressors associated with psychological distress included daily hassles, major negative life events, HIV-related quality of life, and stigma. Protective factors included psychosocial resources such as religious coping, satisfaction with social support, and general coping style and behaviours. Social support and optimism were significantly associated with psychological distress. Findings underscore the need for mental health services for ALHIV in Uganda and other resource-limited settings.